2021
DOI: 10.1057/s42214-020-00088-0
|View full text |Cite
|
Sign up to set email alerts
|

GVC transformation and a new investment landscape in the 2020s: Driving forces, directions, and a forward-looking research and policy agenda

Abstract: Global value chains (GVCs) will undergo substantive transformation in the decade ahead, reshaping the global trade and investment landscape. The change will be driven by five major forces: economic governance realignment, the new industrial revolution, the sustainability endeavor, corporate accountability, and resilience-oriented restructuring. All of this will present challenges and opportunities for firms and states alike, leading to an investment-development paradigm shift. This article discusses the five d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 20 publications
2
52
0
2
Order By: Relevance
“…These regional GVCs will be shorter and less fragmented. In addition, they are likely to involve more concentrated value-added at each stage (Zhan, 2021). Managers of the leading firms in these regional value chains should work to make them more resilient to the current pandemic and inevitable future shocks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These regional GVCs will be shorter and less fragmented. In addition, they are likely to involve more concentrated value-added at each stage (Zhan, 2021). Managers of the leading firms in these regional value chains should work to make them more resilient to the current pandemic and inevitable future shocks.…”
Section: Discussionmentioning
confidence: 99%
“…A number of prominent intellectuals (Enderwick & Buckley, 2020; Gereffi, 2020; Shih, 2020; Zhan, 2021) have suggested that the pandemic will result in a more fragmented and regionalized world economy. They argue that such a configuration might address some of the weaknesses of globalization by introducing global supply chains that combine efficiency with resilience and sustainability (Pananond et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Labor standards may promote social upgrading at the detriment of GVC participation or value capture. As we reflect on the role that GVCs can play on sustainable recovery (Zhan, 2021 ), it is clear that more theoretical and empirical research is needed on the trade-offs and inconsistencies that emerge when GVC-oriented policies are used to address multiple policy goals. Getting a better grasp on these will go a long way in developing a systemic and evidence-based vision of GVC-oriented policies that transcends a government’s or international organization’s ideological heritage.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of global value chains (GVCs), characterized by companies’ fine slicing of the production process across different countries and specializing in specific tasks, has typified the evolution of the global economy since the early 1990s (Zhan, 2021 ). GVC trade in intermediate goods and services produced by different actors in different places in the world grew rapidly until the outbreak of the global financial crisis in 2008, and since then it has stagnated, being affected by the recent increase in protectionism and by the abrupt halt caused by the COVID-19 crisis (Baldwin & Evenett, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In his lead article, Zhan (2021) lays out the significant implications that transforming global value chains (GVCs) can have for the global trade and investment landscape and MNEs' modes of operation. He identifies five major forces that are currently driving GVCs to transform, which include a deepening of geopolitical tensions that is weakening the global governance system, the digitalization of supply chains, sustainability becoming a corporate imperative, firms being increasingly held accountable for their sustainability actions, and socio-economic trends that are globally increasing volatility, uncertainty, complexity and ambiguity (VUCA).…”
Section: Papers In This Special Collectionmentioning
confidence: 99%